COMPARISON OF RADIOGRAPHIC PATTERNS OF KNEE OSTEOARTHRITIS IN TURKISH AND BRITISH PATIENTS: RELATIONSHIP BETWEEN SYMPTOMS AND DISABILITY - Nurdan Kotevoğlu,; Nesrin Canik,; Afitap İçağasıoğlu, (Archives of Rheumatology, 2004)
Osteoarthritis, with different risk factors and classifications is a heterogenous disease. Symptoms poorly correlate with structural damage as seen on plain radiographs. Cultural ( lifestyle ) differences between the populations may also account for some of the differences. In a group of hospital referred British patients with knee OA , bilateral knee joints with the involvement of more than one compartment was observed. Severe and multicompartmental radiographic changes were associated with calcium pyrophosphate crystal deposition, nodal changes, and polyarticular interphalangial ostoearthritis. With a similarly designed study, radiographic patterns of 165 patients were analyzed and looked for associations with clinical findings and disability; besides the results were compared with those of British patients. Presence of nodal changes, chondrocalcinosis, effusions and the presence of previous trauma were more frequent in women. 96 patients (61.2 %) had bilateral knee OA whereas 62 (39.4 %) had unilateral involvement. Isolated patellofemoral involvement was rare with the lowest ratio in lateral OA. Bicompartmental involvement was the most common form both in unilateral and bilateral clinical presentations. Osteophyte was present in 93.9 % of radiographs. On univariate analysis, WOMAC had a correlation with female sex (p<0.05), chondrocalsinosis (p<0.05), night pain (p<0.05) and inactivity stiffness (p<0.05). On multivariate analysis there was a correlation with WOMAC and activity pain (p<0.01), night pain (p<0.01), rest pain (p<0.01), inactivity stiffness (p<0.01), older age (p<0.05) and female sex (p<0.05). Radiographic features were not found associated with any clinical finding or disability. This is an observational study and reflects the characteristics of hospital referred patients, so epidemiological studies will give more data on the clinical, radiological presentations of knee osteoarthritis and possible associations.